Perlindungan Hukum terhadap Pelaku Usaha Online yang Mengalami Kerugian Akibat Konsumen pada Platform Shopee dan Lazada di Kota Kuningan - Adinda Nurul Hawa AbuBakar; Alya Rabila Anjani; Annisa Nurfadilah; Biru Dean Samugra; Dede Rosa Amelia (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
In an increasingly advanced digital era e-commerce has become one of the most rapidly growing economic sectors. The development of e-commerce platforms in Kuningan city such as Shopee and Lazada has provided great opportunities for online businesses. As online business actors not only face challenges in increasing sales and services. However, they must also be able to face the risk of losses incurred by irresponsible consumers. This study aims to explore and examine the legal protection mechanisms available to online business actors between shopee and lazada who experience such losses. The research method used is a qualitative research method in the form of in-depth interviews with online business actors between shopee and lazada to get a comprehensive perspective on this issue. The results of the interviews show that although there are regulations aimed at protecting business actors in accordance with Article 6 of Law No. 8 of 1999 concerning Consumer Protection and become the basis for lawsuits for business actors against consumers who have bad faith. Implementation and law enforcement still experience various obstacles, such as a lack of legal awareness among business actors and a weak law enforcement system. This study suggests the need to increase legal education for business actors and strengthen law enforcement mechanisms to ensure effective protection of online business actors, especially on the Shopee and Lazada platforms. Keywords: Consumer; Loss; Lazada platform; Legal protection; Online business actors; Shopee platform